Ambrosiella catenulata Isolated from Ambrosia Beetles in Korean Apple Orchards - Ju-Heon Lee; Youngsoo Kim; Jong-Taek Park; Dong-Hyuk Lee; Hee-Young Jung (한국균학회지)
A fungus was isolated from ambrosia beetles collected using beetle traps in an apple orchard in Gunwi-gun, Daegu, South Korea. This fungal strain was termed ARI-24-A5, and was identified through morphological characterization and molecular phylogenetic analysis. After 8 d of incubation on potato dextrose agar (PDA), ARI-24-A5 exhibited gray-to-olive coloration, abundant aerial mycelia, and a colony diameter of 72.0–79.0 mm. Morphologically, the aleurioconidiophores formed monilioid chain structures, and the size of the aleurioconidia was 11.1 × 10.8 μm. For precise identification, molecular phylogenetic analysis was performed using the internal transcribed spacer (ITS) region, translation elongation factor 1-alpha (TEF1-α), small subunit of nuclear ribosomal RNA (SSU), and RNA polymerase II subunit 1 (RPB1) gene sequences. The overall analysis confirmed that ARI-24-A5 belongs to the genus Ambrosiella, which is known for its symbiotic relationship with ambrosia beetles. In the phylogenetic tree, ARI-24-A5 shared the same taxonomic position as A. catenulata and its morphological characteristics were consistent with those of this species. Therefore, ARI24-A5 was identified as A. catenulata, making this the first record of this species in South Korea.